Measurement and structural model of agile software development critical success factors - Kukreja, Vinay; Ahuja, Sachin; Singh, Amitoj (International Journal of Engineering and Technology, 2018)
Purpose: Agile methodologies have emerged as an innovative and successful business changing way for software development companies since the success rate for completing the software projects on time and budget is better than conventional methodologies. This study proposes a theoretical framework of success factors for agile software development and validates the proposed framework using structural equation modeling.Design Methodology: A survey based random sampling was performed for data collection from 201 respondents identified from the pool of agile practitioners in software companies. Structural Equation Modeling performed on the collected data to validate measurement model as well as the structural model.Findings: The theoretical model was confirmed with modifications and the results showed that required level of fitness indexes have been achieved for the measurement model and structural model. The validation of the factors has also been done.Originality/Value: This study will guide the agile practitioners, academicians and project managers to focus more on the particular success factors which have high weight towards project success.